Analysis of the Effect of Digital Media Use on Students' Conceptual Understanding of Global Warming - Firna Agustin; Indri Sari Utami; Khairunnisa; Hanum Listiyani; Aufa Ahdina; Nia Septiani; Aisyah Aristawati Sadina; Aden Yusril Sasmita (JoISE : Journal of Intergratet Science Education, 2025)
This study aims to analyze the effect of digital media use on students' conceptual understanding of global warming. The research method used a quantitative approach with a quasi-experimental design and comparative research type, involving two 10th grade classes at SMAN 3 Kota Serang, namely an experimental class with 36 students who received learning using digital media in the form of interactive PPT, videos, and educational games based on Canva, and a control class with 35 students who learned using conventional methods. Data analysis was conducted through normality tests, homogeneity tests, and Mann-Whitney U non-parametric tests. The Mann-Whitney test results showed an Asymp. Sig. (2-tailed) value of 0.000 < 0.05, confirming a significant difference between the experimental class and the control class. Descriptively, the experimental class obtained a higher average score (87.67) with a median of 100 and a more consistent distribution of scores compared to the control class (63.46 with a median of 75). These findings indicate that digital media can visualize abstract concepts, reduce cognitive load, and increase student engagement in learning. The practical impact of this study recommends that teachers integrate digital media into science learning to reduce misconceptions and increase learning motivation, while theoretically strengthening the constructivism and cognitive load theory frameworks in explaining how educational technology supports concept understanding.